Determining anatomically-safe corridors for placement of lateral mass screws in the first cervical vertebra of the Emirati population – a CT study - Dineshwary Suresh; Nerissa Naidoo; Rashid AlSharhan; Usama Al Bastaki; Jeyaseelan Lakshmanan; Baylis Vivek Joseph; Ivan James Prithishkumar (Scientific Reports)
Abstract The first cervical vertebra (C1) is atypical in shape and bears a complex relationship with important neurovascular structures such as the vertebral artery and cervical spinal cord which are at risk of injury during misplaced screw fixation of C1. Placement of screws into the lateral mass of C1 vertebra is performed for stabilization of the craniovertebral junction. The objective of this study was to describe ideal screw dimensions, precise entry points, safe bony corridors, and ideal trajectories for placement of lateral mass screws in the Emirati population. CT scans of 160 Emirati patients (> 18 years) were studied and variables relevant to lateral mass screw fixation were measured. Screw entry at the centre of lateral mass, below its junction with the posterior arch, allowed straight screws of lengths of 20 mm and 19.5 mm in Emirati males and females, respectively. A medial angulation of 20° in males and 15° in females allowed maximum bone purchase. Screw entry at the junction of medial margin of posterior arch and lateral mass allowed straight screws of length 18 mm in both males and females. We recommend safe cephalic angulations of 19° and 16°in males and females, respectively. The mean critical width was 7.6 mm in males and 6.8 mm in females which would safely permit screws of width 4.0 mm. Pre-operative knowledge of the above dimensions would help in greater precision, minimizing the risk of injury to neurovascular structures in the vicinity of C1 lateral mass.